Opposition parties in European legislatures conflict or consensus? - De Giorgi, Elisabetta; Ilonszki, Gabriella (Routledge studies on political parties and party systems, 2018)
Democratic theory considers it fundamental for parties in government to be both responsive to their electorate and responsible to internal and international constraints. But recently these two roles have become more and more incompatible with Mair's growing divide in European party systems between parties which claim to represent, but don't deliver, and those which deliver, but are no longer seen to represent truer than ever. This book contains a qualitative and quantitative analysis of the behaviour of the opposition parties in eleven European democracies across Western and East Central Europe. Specifically, it investigates the parliamentary behaviour of the opposition parties, and shows that the party context is increasingly diverse. It demonstrates the emergence of two distinct types of opposition: one more cooperative, carried out by the mainstream parties (those with government aspirations), and one more adversarial focusing on government scrutiny rather than on policy alternatives (parties permanently excluded from power). It systematically and analytically explores the sources of their behaviour, whilst acknowledging that opposition is broader than its mere parliamentary behaviour. Finally, it considers the European agenda and the economic crisis as two possible intervening variables that might have an impact on the opposition parties' behaviour and the government-opposition relations. As such, it responds to questions that are major concerns for the European democracies of the new millennium. This text will be of key interest to students and scholars of political parties, European politics, comparative politics and democracy